Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.5173/ceju.2018.1695
|View full text |Cite
|
Sign up to set email alerts
|

Testis Sparing Surgery For Small Testicular Masses and Frozen Section Assessment

Abstract: IntroductionWe present our experience with patients who had suspected testicular masses, managed by a frozen section assessment and testicular sparing surgery.Material and methodsWe performed a retrospective review of all patients over the last 5 years, who underwent a frozen section assessment and testicular sparing surgery for small testicular lesions. The frozen section assessment was compared with the final histology.ResultsTwelve patients were identified. The mean age of patients was 40 years (22–58 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Our results showed that FSE is highly reliable for detecting malignant lesions throughout the reported case series, reaching 100% accuracy in 25 out of 38 studies (66%) [ 8 , 10 , 12 , 13 , 14 , 15 , 16 , 17 , 22 , 25 , 26 , 29 , 31 , 34 , 35 , 40 , 42 , 43 , 46 , 48 , 51 , 53 , 55 , 57 , 58 ]. Good accuracy was also reported in five studies, namely, by Connolly and colleagues (96.1%) [ 49 ], in the 14 years of experience reported by Silverio et al (96%) [ 56 ], by Matei et al (93%) [ 54 ], in an earlier study by Dell’Atti (84.3%) [ 50 ] and by Ferretti et al (83.33%) [ 52 ].…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Our results showed that FSE is highly reliable for detecting malignant lesions throughout the reported case series, reaching 100% accuracy in 25 out of 38 studies (66%) [ 8 , 10 , 12 , 13 , 14 , 15 , 16 , 17 , 22 , 25 , 26 , 29 , 31 , 34 , 35 , 40 , 42 , 43 , 46 , 48 , 51 , 53 , 55 , 57 , 58 ]. Good accuracy was also reported in five studies, namely, by Connolly and colleagues (96.1%) [ 49 ], in the 14 years of experience reported by Silverio et al (96%) [ 56 ], by Matei et al (93%) [ 54 ], in an earlier study by Dell’Atti (84.3%) [ 50 ] and by Ferretti et al (83.33%) [ 52 ].…”
Section: Resultsmentioning
confidence: 65%
“…Ultimately, 57 studies were included in the final list. Thirty-nine of them described cases of impalpable testicular masses diagnosed incidentally by US [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], and 47 included information about the histology of small testicular masses that underwent surgical treatment [ 5 , 6 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 24 , 25 , 26 , 28 , 29 , 30 , 31 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation